Building a society conducive to the use of corporate social responsibility as a tool to develop disaster resilience with sustainable development as the goal: an interpretive structural modelling approach in the Indian context - Repaul Kanji; Rajat Agrawal (Asian Journal of Sustainability and Social Responsibility (AJSSR), 2019)
The indomitable spirit of growth of mankind has led to rapid urbanisation and development, steered by industries and corporates. Whether development begets disaster or disaster begets development, is still a matter of on-going discussions and debates, but, each time the society takes a catastrophic hit, humanity begs to question the role of corporate in disaster mitigation, management and rehabilitation. The Companies Act, 2013 of India has steered India into becoming one of the few countries with a mandatory CSR regime. This study finds its genesis in the logical question that follows this premise; since expenditure through CSR is already mandatory in India and is directed towards sustainable development, why not channel such investments in such a manner that disaster resilience becomes inclusive of the final objective of sustainable development? The purpose of this study is to identify those crucial elements of our society and their inter-dependencies which when ideally tweaked and nurtured will lead to a social setup where CSR investments would lead to sustainable development inclusive of disaster resilience. Extensive literature followed by questionnaire survey and interviews were used as a tool to judge and evaluate societal enablers and then they were subjected to interpretive structural modelling which brought out the contextual relationships among the enablers. The resultant model is a hierarchical structure of enablers, revealing their inter-dependencies and relations with each-other. This can help enterprises, corporates, policymakers to understand how to leverage the mandatory CSR regime of India in their favour as well as to create disaster resilience.
Keywords: 650; Corporate social responsibility; interpretive structural modelling; disaster resilience and risk reduction